DEKONSTRUKSI AKUNTANSI PERTANGGUNGJAWABAN SOSIAL DALAM PERSPEKTIF PANCASILA - Harmadji, Dwi Ekasari (Magister Manajemen Universitas Wisnuwardhana, 2019)
The purpose of writing this article is to deconstruct social responsibility accounting in the perspective of Pancasila. At present, the form of social responsibility accounting outcomes is the sustainability report (CSR). The results of this study are the need to increase the understanding of accounting / financial professionals / practitioners of sustainability reporting as the application of the substantive goals of the company concerned, and not a symbolic objective to obtain legitimacy from stakeholders. Increased understanding of spiritual conditions and aspects, economic aspects, social aspects and environmental aspects that must be disclosed in a full and transparent sustainability report, so that it is known by all stakeholders. Keywords: Social Responsibility Accounting, Pancasila